Correlation between dissociation and catalysis of SARS-CoV main protease - Lin, Pei-Ying (Arch Biochem Biophys, 2008)
The dimeric interface of severe acute respiratory syndrome coronavirus main protease is a potential target for the anti-SARS drug development. We have generated C-terminal truncated mutants by serial truncations. The quaternary structure of the enzyme was analyzed using both sedimentation velocity and sedimentation equilibrium analytical ultracentrifugation. Global analysis of the combined results showed that truncation of C-terminus from 306 to 300 had no appreciable effect on the quaternary structure, and the enzyme remained catalytically active. However, further deletion of Gln-299 or Arg-298 drastically decreased the enzyme activity to 1–2% of wild type (WT), and the major form was a monomeric one. Detailed analysis of the point mutants of these two amino acid residues and their nearby hydrogen bond partner Ser-123 and Ser-139 revealed a strong correlation between the enzyme activity loss and dimer dissociation.